A Motivator's Taboo Words in Garyvee’s IGTV - Rahmah, Laily (English Literature Study Program, 2022)
Taboo words on social media are often used for various purposes. In certain cultures, taboo words may be considered offensive and shameful. In addition, taboo words are also used to emphasize something, which means that not all of taboo words are considered as negative words. Therefore, a public figure named Gary used taboo words to express his opinion and provide motivation through his posts on Instagram. Methodologically, this research was included in qualitative descriptive research. In general, this study examined the use of taboo words with the aim of identifying the different types and functions of taboo words in a motivator's post on Instagram using the theory of types of taboo words by Batistella (2005) and the functions of taboo words by Wardhaugh (2006). The findings in this study revealed that Garyvee used 3 types of taboo words, namely obscenity, epithets, and profanity. From a total of 36 data, there were 27 obscenities, 2 epithets, and 1 profanity. However, this study also found that although taboo words were literally considered as negative words, in Garyvee's case, it was found that taboo words could have both negative and positive meanings. Furthermore, in this study, from the 4 functions of taboo words, 3 functions were found, namely to be provocative, to draw attention, and to show contempt. The most common function found in the findings was to draw attention to other people because in this case taboo words were used to express the speaker's messages and attract the audiences to keep giving attention on the motivator's contents.